2022
DOI: 10.3390/vaccines10020276
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding-RNA-Based Therapeutics with an Emphasis on Prostatic Carcinoma—Progress and Challenges

Abstract: Noncoding RNAs (ncRNAs) defy the central dogma by representing a family of RNA molecules that are not translated into protein but can convey information encoded in their DNA. Elucidating the exact function of ncRNA has been a focus of discovery in the last decade and remains challenging. Nevertheless, the importance of understanding ncRNA is apparent since these molecules regulate gene expression at the transcriptional and post-transcriptional level exerting pleiotropic effects critical in development, oncogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Since ncRNAs have a functional role in modulating the expression of multiple downstream gene targets and associated pathways in cancer and other diseases, there is a rationale that suggests that ncRNAs-based therapies are promising as therapeutic options [176]. Different ncRNA-based strategies have been proposed for therapeutical purposes: small interfering RNAs (siRNAs), antisense oligonucleotides (ASOs), short hairpin RNAs (shRNAs), anti-microRNAs (anti-miRNAs), miRNA mimics, miRNA sponges, therapeutic circular RNAs (cirRNAs), and CRISPR-Cas9-based gene editing [281]. Several clinical trials have confirmed that ncRNAs are successful for the treatment of complex diseases including cancer [176,282].…”
Section: Potential Role Of Ncrnas As Therapeutic Agents In Exposome-a...mentioning
confidence: 99%
“…Since ncRNAs have a functional role in modulating the expression of multiple downstream gene targets and associated pathways in cancer and other diseases, there is a rationale that suggests that ncRNAs-based therapies are promising as therapeutic options [176]. Different ncRNA-based strategies have been proposed for therapeutical purposes: small interfering RNAs (siRNAs), antisense oligonucleotides (ASOs), short hairpin RNAs (shRNAs), anti-microRNAs (anti-miRNAs), miRNA mimics, miRNA sponges, therapeutic circular RNAs (cirRNAs), and CRISPR-Cas9-based gene editing [281]. Several clinical trials have confirmed that ncRNAs are successful for the treatment of complex diseases including cancer [176,282].…”
Section: Potential Role Of Ncrnas As Therapeutic Agents In Exposome-a...mentioning
confidence: 99%